Lapvona - Moshfegh, Ottessa 1981- (Random House, 2022)
"In a village in a medieval fiefdom buffeted by natural disasters, a motherless shepherd boy finds himself the unlikely pivot of a power struggle that puts all manner of faith to a savage test, in a spellbinding novel that represents Ottessa Moshfegh's most exciting leap yet Little Marek, the abused and delusional son of the village shepherd, never knew his mother; his father told him she died in childbirth. One of life's few consolations for Marek is his enduring bond with the blind village midwife, Ina, who suckled him when he was a baby, as she did so many of the village's children. Ina's gifts extend beyond childcare: she possesses a unique ability to communicate with the natural world. Her gift often brings her the transmission of sacred knowledge on levels far beyond those available to other villagers, however religious they might be. For some people, Ina's home in the woods outside of the village is a place to fear and to avoid, a godless place. Among their number is Father Barnabas, the town priest and lackey for the depraved lord and governor, Villiam, whose hilltop manor contains a secret embarrassment of riches. The people's desperate need to believe that there are powers that be who have their best interests at heart is put to a cruel test by Villiam and the priest, especially in this year of record drought and famine. But when fate brings Marek into violent proximity to the lord's family, new and occult forces upset the old order. By year's end, the veil between blindness and sight, life and death, the natural world and the spirit world, will prove to be very thin indeed"--
Auf dem Umschlag: "A novel"
Keywords: Novels; Fiktionale Darstellung